The Application of The Corporate Governance In Management of Islamic Banks - Rahma, Al Siddig Talha M.; Musa, Durria Hyder Siddeg (Archives of Business Research, 2020)
One of the most issues noticed by researchers and suggested from investors is Corporate Governance, addressing the need for company management control, dividing economical unit from its ownership and improving the performance of the board of managers, auditors, accounting system, internal control, and finally maintaining investors and stakeholders' rights. Using better managers in companies results in improvement of their performance. So the purpose of this paper comes to examine the determinants of the Islamic bank's product and services disclosure strengths and weaknesses of corporate governance. , and suggest ways in which can be improved, the results reported across perspective and levels of analyses through, global, regional, legal systems, regularity quality and bank size. The results indicate that the strongest theme of corporate governance for Islamic banks in the sample is Transparency and Disclosure, followed by Internal Controls and External Audit. At the other extreme, the weakest corporate governance theme is Risk Governance, followed by Shariah Governance and the Boards of Directors .